Could microalgae be a strategic choice for responding to the demand for omega-3 fatty acids? A European perspective. (March 2022) - Magoni, Chiara; Bertacchi, Stefano; Giustra, Chiara Maria; Guzzetti, Lorenzo; Cozza, Radiana; Ferrari, Michele; Torelli, Anna; Marieschi, Matteo; Porro, Danilo; Branduardi, Paola; Labra, Massimo
Abstract: Background: Omega-3 fatty acids (FAs) are relevant commodities in the market due to their important role in human wellbeing. As the worldwide demand is increasing, alternative sources and sustainable processes are needed to face the limited supply of the omega-3 FAs of fish origin. Microalgae provide a portfolio of biodiversity able to satisfy the quest for alternative sources and to match the need of sustainability for the production of these compounds. Scope and approach: This review deepens the topic of sustainable production and supply chain by analyzing the current data available in scientific literature and providing a glance of the market of omega-3 FAs from different microalgal species. This was assessed in the light of the technologies applicable to enhance and improve production. We analyzed and compared how traditional and innovative biotechnological approaches are exploited to maximize the ability of microalgae to produce omega-3 FAs, especially eicosapentaenoic acid and docosahexaenoic acid (EPA and DHA). Key findings and conclusions: This critical overview highlights that microalgal bioprospecting, combined with engineering approaches and with the study of the influence from the environment, can provide a reliable and sustainable alternative for omega-3 FAs production. Unlocking the interdependence of these factors will play a key role in achieving the industrial scalability and standardization of the processes. Finally, the strategy to promote the consumer's acceptability of algae-based products will also be pivotal to substitute the current sources of omega-3 FAs and therefore to address the sustainability challenges that Europe, as well as the rest of the world, is facing. Highlights: The increasing demand for omega-3 fatty acids pushes for sustainable supply chains. Microalgal biodiversity is a natural reservoir to be exploited for omega-3 production. Biotech approaches combined with genetic modification techniques fosters the sector. The legal framework is pivotal to understand the fate of microalgal market in the EU.